Evolutionary dynamics and global spread of macrolide-resistant Bordetella pertussis during the post-pandemic pertussis resurgence - Zhang, Haodong; Kang, Zhihua; Zhang, Yingying; Yang, Yuanbin; Li, Huiwen; Wang, Naike; Wang, Jiancheng; Jiao, Fuxing; Tong, Shanwei; Wang, Bingsong; Gao, Song; Ni, Chengpei; et al. (Elsevier BV, 2026)
Objectives: A global resurgence of pertussis has followed the COVID-19 pandemic, yet the underlying drivers remain unclear. We investigated the contribution of Bordetella pertussis genomic evolution to the post-pandemic resurgence.
Methods: We analyzed 8117 B. pertussis genomes from 35 countries, including 249 newly sequenced isolates collected from six regions in China. Temporal dynamics of genotypes, antigenic profiles, and macrolide resistance were examined before, during, and after the pandemic.
Results: Shared post-pandemic evolutionary patterns were identified across global B. pertussis populations. These included the emergence of macrolide-resistant strains in France, the United States, and Australia, and their dominance in eastern China, driven by the expansion of the MR-MT28 sublineage (ptxP3/fim3-1/prn150 or PRN-deficient). Parallel antigenic shifts were observed, with declining PRN-deficient strains accompanied by increasing prn2 allele frequencies in multiple regions. Region-specific dynamics were also evident. In China, the post-pandemic resurgence was characterized by near-complete replacement of circulating strains by the MR-MT28 sublineage. In contrast, the resurgence in Europe and the United States largely reflected the persistence and expansion of locally established lineages. Expanded sampling further revealed that MR-MT28 sublineage is no longer genetically homogeneous, having diversified into multiple phylogenetic groups, with most isolates detected outside China (72%, 8/11) being PRN-deficient.
Conclusions: This unified global genomic analysis demonstrates both shared and region-specific post-pandemic shifts in B. pertussis populations. The dominance of the MR-MT28 sublineage in China, together with its international dissemination and ongoing diversification, represents a growing public health concern and underscores the need for coordinated global genomic surveillance.